The Effectiveness of informational Services Through Small Group Discussion to Improve Students Tolerance Attitudes - Sally Putri Karisma; Neviyarni Neviyarni; Solfema Solfema (International Journal of Applied Counseling and Social Sciences, 2020)
Tolerance is very important to maintain diversity in Indonesia, so it needs to be grown early. Students need to have tolerance to respect each other, accept and acknowledge the differences and diversity of religions, ethnicities, beliefs and opinions of others. This study aims to determine the effectiveness of information services with a small group discussion approach to improve student tolerance. The sample of this study consisted of 36 students selected by cluster random sampling techniques. The instrument used was a tolerance scale with a reliability of 0.844. Data analysis in this study used a one group pretest-posttest approach. The results showed that students have a very high attitude of tolerance, with an average achievement of 97.22%. The implications of this study are as a basis for counselors to improve student tolerance.